Pengaruh Terapi Murottal Al-Qur’an Dan Benson Terhadap Tingkat Fatigue Pada Pasien Hemodialisis - Nuryanti, Nuryanti; Bayhakki, Bayhakki; Deli, Hellena (Innovative: Journal Of Social Science Research, 2024)
Patients suffering from chronic kidney disease (CKD) are required to undergo hemodialysis for life. Often, hemodialysis patients face both physical and psychological issues, one of which is fatigue. This study aims to determine the effect of Murottal Al-Qur’an and Benson therapy on the fatigue levels of hemodialysis patients. Methods: This research uses a quasi-experimental design with a pre-test/post-test control group design. The sample consisted of 32 respondents selected based on inclusion criteria using purposive sampling technique. The analysis employed bivariate analysis using paired t-test and independent t-test. Of the 32 respondents, the majority were male, totaling 18 respondents (56.3%). The most common age group was 45-60 years, with 13 respondents (40.6%), and the majority of respondents were Muslim, totaling 26 respondents (81.3%). The highest level of education among respondents was high school, with 13 respondents (40.6%). Statistical test results showed a p-value of 0.034, which is <α=0.05, leading to the rejection of the null hypothesis (H0). It means, there is an effect of Murottal Al-Qur’an and Benson therapy on the fatigue levels of hemodialysis patients.